TR Locus Annotation and Characteristics of Rhinolophus ferrumequinum - Zhou, Hao; Ma, Long; Liu, Longyu; Yao, Xinsheng (Frontiers in Immunology, 2021)
T-cell antigen receptors (TRs) in vertebrates can be divided into αβ or γδ, encoded by TRA/D, TRG, or TRB loci. TRs play a central role in mammal cellular immunity, which occurs by rearrangement of V, D, J, and C genes in the loci. The bat is the only mammal with flying ability and is considered the main host of zoonotic viruses, an important public health concern. However, at present, little is known about the composition of bat TR genes. Based on the whole genome sequence of the greater horseshoe bat (Rhinolophus ferrumequinum) and referring to the TR/IG annotation rules formulated by the international ImMunoGeneTics information system (IMGT), we present a complete annotation of TRA/D, TRG, and TRB loci of R. ferrumequinum. A total of 128 V segments, three D segments, 85 J segments, and 6 C segments were annotated and compared with other known mammalian data. The characteristics of the TR locus and germline genes of R. ferrumequinum are analyzed.